Night pleasures - Kenyon, Sherrilyn, 1965- (New York : St. Martin's Press, 2009)
Vampire Kyrian of Thrace is handcuffed to beautiful accountant Amanda as part of a dangerous adversary's cat-and-mouse game, a confrontation for which the fate of the world hangs in the balance.
edited hb 2015-06-16
Keywords: Vampires -- Fiction; Romantic suspense fiction